1990
DOI: 10.1111/j.1574-6968.1990.tb03821.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytolethal distending toxin (CLDT) production by enteropathogenic Eschrichia coli (EPEC)

Abstract: Culture supernates of 16 strains of EPEC belonging to 6 different serogroups, when assayed on Chinese Hamster Ovary (CHO) cells up to 96–120 h, induced distinct morphological changes. The supernate activities were heat‐labile, unrelated to heat‐labile enterotoxin (LT), verotoxin (VT), or hemolysin, did not show necrosis in rabbit skin and caused no fluid secretion in the rabbit ileal loop assay (RILA). Simulatneous production of CLDT and heat‐stable enterotoxin (ST) were detected in four EPEC strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 15 publications
4
30
0
Order By: Relevance
“…These results clearly show that CDT production is not limited to EPEC strains, as some epidemiological studies have suggested (1,2,6,17).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These results clearly show that CDT production is not limited to EPEC strains, as some epidemiological studies have suggested (1,2,6,17).…”
Section: Discussionsupporting
confidence: 63%
“…The culture filtrates of CDT-producing E. coli strains induced characteristic morphological changes, and the distended cells died in 3 to 4 days (23). CDT production was reported from various serotypes of enteropathogenic E. coli (EPEC) (2,6,17) and from several bacterial species of medical importance (10,26,32,37). The CDTs induce the formation of giant mononucleated cells of sensitive eukaryotic cell lines and block the cell cycle in G 2 phase (3,30).…”
mentioning
confidence: 99%
“…In fact, in a survey of CDT production by EPEC serogroups O55, O86, O119, O126, O127 and O142, Guth et al (1994) found that only O86:H34 strains produced CDT. CDT producing strains have been reported among E. coli strains isolated in Canada and India, although in one of these studies serotyping was not performed (Bouzari et al 1990) and in the other one, a single CDT positive strain of serotype O86:H34 was found (Johnson & Lior 1988a). A significant percentage of CDT producing strains belonging to the same serotype has not been reported so far.…”
Section: Discussionmentioning
confidence: 88%
“…However, none of the virulence genes except for the astA gene were detected by PCR and DNA probes ( Table 2). Although there are several reports regarding the isolation of Cdt-producing E. coli from diarrheal patients in developing countries (1,2,4,9,14,15,17), little is known about the incidence of Cdt-produing E. coli in diarrheal cases in developed countries including Japan (3,10,20,22). To our knowledge, this is the first report demonstrating the possible association of Cdt-producing E. coli from a diarrheal patient, particularly from a bloody diarrheal case, in Japan.…”
mentioning
confidence: 90%